A smart avatar tutor for mimicking characters of Bangla sign language - Islam, Apu; Rahman, Somaya Al Sadia; Bhowmick, Pratick (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.